Experimental Study of The Effect of Reactor Temperature Variations on The Characteristics of Oil Resulting from The Pyrolysis Method of Crumb Rubber Solid Waste - Puspawan, Angky; Supardi, Nurul Iman; Gunawan, Agustin; Mubarok, Abdul Latif; Sulthan, Rifki (Universitas Muhammadiyah Metro, 2025)
Energy is an important part of human life because almost all human activities always require energy. Therefore, it is necessary to conduct research to overcome the above problems, namely by making alternative energy by utilizing crumb rubber plant waste into alternative oil. The crumb rubber solid waste that we use comes from the micro blending and macro blending milling process from the process there is waste in the form of granulated rubber (Crumb Rubber Waste). Crumb Rubber Plant waste is currently not being utilized optimally. The basic structure of natural rubber is a linear chain of isoprene units (C5H8) natural rubber is a polymer of hydrocarbon compounds, namely 2–methyl-1,3 butadiane (isoprene). The main purpose of this study is to determine the value of the oil combustion rate resulting from the pyrolysis of crumb rubber solid waste and find out the characteristics of the oil resulting from the pyrolysis of crumb rubber solid waste and find out the comparison of the quality of oil from crumb rubber solid waste. From this study will show the optimum amount of pyrolysis and distillation results to produce oil. Operating conditions take place at atmospheric pressure with temperature variations of 200oC, 250oC, 300oC, and 350oC for 180 minutes for the pyrolysis process which will then be distilled with a temperature of 95°C for 20 minutes. The results showed that % of the conversion of raw materials into oil (amendment) was highest for the pyrolysis process at a temperature of 350oC of 51.86% while in the distillation process pyrolysis oil with a temperature of 350oC as much as 82.55%. For the value of the combustion rate in the largest pyrolysis process with a value of 0.975 at a temperature of 350oC and a distillation process of 1,612 at a temperature of 350oC.